Superovulation in Murrah Buffaloes - SINGH, A K; NARAYANA, K (The Indian Journal of Animal Reproduction, 2023)
Superovulation of buffaloes is a criticalfactor in the embryo transfer industry.Several gonadotrophins have been used tostimulate follicular development in buffaloes,with large variability in ovulatory response.The present study was done to assessthe superovulatory response to pFSH inbuffaloes. Nine Murrah buffaloes with apalpable corpus luteum were givenintramuscular (i.m.) injection of Luprostiol15mg (Prosolvin, lntervet, Holland) andmonitered for the onset of oestrus usinga companion bull. Day zero was taken asDay of oestrus.
Keywords: Superovulation; Murrah Buffaloes